PELUANG DAN PENERAPAN LOGISTIK HALAL DI INDONESIA DALAM RANTAI PASOK MAKANAN - Mohammad Zuhurul Fuad; Emma Atmawati (TAKAFUL: Jurnal Ekonomi Dan Perbankan Syariah, 2025)
This article discusses the opportunities and application of halal logistics in Indonesia in the food supply chain. The term halal logistics refers to the process of managing the flow of goods, storage, and distribution of resources from the starting point to the end point in the supply chain in accordance with the application of sharia principles. These principles are the difference between conventional logistics and halal logistics. This research shows that the halal food industry in Indonesia has great potential to be developed, supported by the largest Muslim population in the world. The emergence of halal issues is the main motivator driving the adoption of halal logistics. However, the implementation of halal logistics still faces several challenges, such as the lack of adequate infrastructure, lack of understanding of business actors, and limited trained human resources. Based on the findings of this study, the practical implication is that it can help the government as a policy maker to recognise the problems that need to be addressed in encouraging logistics companies to switch to halal practices. In addition, this article presents strategies for implementing halal logistics in Indonesia so that it can compete in the global realm. Such as the need to increase the capacity of human resources in managing halal food supply chains, the development of appropriate infrastructure, and socialisation in various regions to increase public understanding of halal issues.